DIAGNOSTIC EFFECTIVENESS OF A NEW METHOD FOR COMPREHENSIVE ASSESSMENT OF THE DEGREE OF HIP DYSPLASIA IN CHILDREN - V. V. Zotkin; D. I. Anisimov; E. A. Anisimova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Using clinical, radiological, neuromiographic, and biomechanical data, we have developed an original system for comprehensive assessment of hip dysplasia degree in children. Its sensitivity and specificity was 95.6% and 87.5 % respectively; its overall accuracy was 95.1%; its validity was as follows: Сr–0.89; Cs–0.86; Cc–0.85.